Innovations in Social Marketing and Public Health Communication Improving the Quality of Life for Individuals and Communities - Wymer, Walter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume presents the most current theoretical advances in the fields of social marketing and public health communications. The volume is divided in two parts. Part 1 contains chapters pertaining to research and theory reflecting improvements and contributions to theories that help improving quality of life. It includes literature reviews, conceptual research and empirical studies on social marketing communications, models to understand individual’s risky behaviors, and how to improve social interventions. The second part emphasizes applied research, consisting of best practices, applied experiments, and case studies on social marketing innovative practices with implications for quality of life.
Part I. Theoretical Developments -- Chapter 1. Formulating Effective Social Marketing and Public Health Communication Stategies; Walter Wymer -- Chapter 2. Using Publicity to Enhance the Effectiveness of a Child Obesity Prevention Program; Simone Pettigrew, Lisa Weir, Mark Williams and Sharyn Rundle-Thiele -- Chapter 3. Digital Innovation in Social Marketing: A Systematic Literature Review of Social Marketing Interventions Using Digital Channels for Engagement; Krysztof Kubacki, Sharyn Rundle-Thiele, Lisa Schuster, Carla Wessels, Naomi Gruneklee -- Chapter 4. Does context matter? Australian Consumers’ Attitudes to the Use of Messages and Appeals in Commercial and Social Marketing Advertising; Sandra Jones and Katherine Eagleton -- Chapter 5. Internal Social Marketing, Servicescapes and Sustainability: A Behavioural Infrastructure Approach; Linda Brennan, Wayner Binney and John Hall -- Chapter 6. Faces of Power, Ethical Decision Making and Moral Intesity; Jan Brace-Govan -- Chapter 7. Social Influence and Blood Donation: Cultural Differences between Scotland and Australia; Rebekah Russell-Bennett, Geoff Smith, Kathleen Chell and Jennifer Goulden -- Chapter 8. On Dreching the Massive, Mature Tourist Destinations in the Sunny and Sandy Social Marketing Innovation; Gonzalo Diaz Meneses and Ignacio Luri Rodríguez -- Chapter 9. Innovations in Social Marketing and Public Health Communication: Improving Quality of Life for Individuals and Communities; Marlize Terblanche-Smit and Nic Terblanche -- Chapter 10. Behavioural Factors Determining Fruit Consumption in Adolescents and Characteristics of Advertising Campaigns towards Possible Increased Consumption; Joana Gidinho and Helena Alves -- Part II. Applied Research -- Chapter 11. Promoting Mental Health and Well-Being in Individuals and Communities: The 'Act-Belong-Commit' Campaign; Rob Donovan and Julia Anwar-Henry -- Chapter 12. Preparation without Panic: A Comprehensive Social Marketing Approach to Planning for a Potential Pandemic; Sandra Jones, Don Iverson, Max Sutherland, Chris Puplick, Julian Gold and Louise Waters -- Chapter 13. FASD Prevention Interventions Valued by Australian and Canadian Women; Sharyn Rundle-Thiele, Robin Thurmeier, Sameer Deshpande, Magdalena Cismaru, Anne Lavack, Noreen Agrey and Renata Anibaldi -- Chapter 14. Does Social Marketing Have a Role in Skin Cancer; Tim Crowley and Maurice Murphy -- Chapter 15. Tomorrow's World: Collaborations, Consultations and Conversations for Change; Sinead Duane, Christine Domegan and Patricia McHugh -- Chapter 16. 'Working without Occupational Health and Safety is a Thing of the Past': The Effectiveness of a Workplace Health and Safety Campaign in Andalusia (Spain); María José Montero-Simó, Rafael Araque-Padilla and Juan Miguel Rey Pino -- Chapter 17. Improving Quality of Life by Preventing Obesity; Tatiana Levit, Lisa Watson and Anne M. Lavack -- Chapter 18. The One to One Movement: The New Social Business Model; M. Isabel Sánchez-Hernández -- Chapter 19. The Nature of Family Decision Making at the Bottom of the Pyramid (BoP) - Social and Managerial Implications; Shruti Gupta and christina Sesa -- Chapter 20. Designing Social Marketing Activities to Impact the Shaping of Expectations of Migrants in Health Service Encounters: The Case of African Migrant Blood Donation in Australia; Ahmed Ferdous, Michael Polonsky, Bianca Brijnath and Andre Renzaho -- Chapter 21. Sustainability Marketing: Reconfiguring the Boudaries of Social Marketing; Ken Peattie.
Keywords: Quality of life; Marketing; Medical research; Quality of Life Research; Marketing; Quality of Life Research